Very easy

Calculus Level 2

Can you solve it?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Justin Tuazon
Nov 8, 2014

A = ( 5 2 6 + 9 6 2 ) ( 6 + 2 ) = ( 3 2 + 9 2 18 ) ( 6 + 2 ) = ( 3 2 + 6 3 ) ( 6 + 2 ) = ( 6 2 ) ( 6 + 2 ) = 6 2 = 4 A = 4 A=(\sqrt { 5-2\sqrt { 6 } } +\sqrt { 9-6\sqrt { 2 } } )(\sqrt { 6 } +\sqrt { 2 } )\\ \\ =(\sqrt { 3 } -\sqrt { 2 } +\sqrt { 9-2\sqrt { 18 } } )(\sqrt { 6 } +\sqrt { 2 } )\\ \\ =(\sqrt { 3 } -\sqrt { 2 } +\sqrt { 6 } -\sqrt { 3 } )(\sqrt { 6 } +\sqrt { 2 } )\\ \\ =(\sqrt { 6 } -\sqrt { 2 } )(\sqrt { 6 } +\sqrt { 2 } )=6-2=4\\ \\ \therefore \quad \boxed { A=4 }

Hello,

Use calculator = answer....

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...